Principles of soil chemistry - Tan, Kim H. (Boca Raton : CRC Press, 2011)
Summary: "Learn the secrets of soil chemistry and its role in agriculture and the environment. Examine the fundamental laws of soil chemistry, how they affect dissolution, cation and anion exchange, and other reactions. Explore how water can form water-bridges and hydrogen bonding, the most common forces in adsorption, chelation, and more. Discover how electrical charges develop in soils creating electrochemical potentials forcing ions to move into the plant body through barriers such as root membranes, nourishing crops and plants. You can do all this and more with Principles of Soil Chemistry, Fourth Edition. Since the first edition published in 1982, this resource has made a name for itself as a textbook for upper level undergraduates and as a handy reference for professionals and scientists. This fourth edition reexamines the entire reach of soil chemistry while maintaining the clear, concise style that made previous editions so user-friendly. By completely revising, updating, and incorporating a decade's worth of new information, author Kim Tan has made this edition as an entirely new and better book."--Publisher's description.
First ed. published 1982.
Keywords: Soil chemistry